2017
DOI: 10.18632/oncotarget.16203
|View full text |Cite
|
Sign up to set email alerts
|

CD24 Expression and differential resistance to chemotherapy in triple-negative breast cancer

Abstract: Breast cancer (BC) is a leading cause of cancer-related death in women. Adjuvant systemic chemotherapies are effective in reducing risks of recurrence and have contributed to reduced BC mortality. Although targeted adjuvant treatments determined by biomarkers for endocrine and HER2-directed therapies are largely successful, predicting clinical benefit from chemotherapy is more challenging. Drug resistance is a major reason for treatment failures. Efforts are ongoing to find biomarkers to select patients most l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 58 publications
(65 reference statements)
5
35
0
Order By: Relevance
“…We suggest that the regulation of Src and STAT3 activity by SOX2 via CD24 is a novel mechanism of adaptive resistance toward BRAFis in melanoma cells. [38][39][40][41] This is in line with our data demonstrating that in melanoma cells an increased expression level of SOX2 or CD24 resulted in a higher tolerance toward BRAFis, while the depletion of SOX2 via KD showed higher sensitivity. Several studies have shown that CD24 and SOX2 are associated with a more undifferentiated and more cancer stem cell-like phenotype.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We suggest that the regulation of Src and STAT3 activity by SOX2 via CD24 is a novel mechanism of adaptive resistance toward BRAFis in melanoma cells. [38][39][40][41] This is in line with our data demonstrating that in melanoma cells an increased expression level of SOX2 or CD24 resulted in a higher tolerance toward BRAFis, while the depletion of SOX2 via KD showed higher sensitivity. Several studies have shown that CD24 and SOX2 are associated with a more undifferentiated and more cancer stem cell-like phenotype.…”
Section: Discussionsupporting
confidence: 83%
“…7,36,37 Both SOX2 and CD24 have also been linked to an increased therapy resistance. [38][39][40][41] This is in line with our data demonstrating that in melanoma cells an increased expression level of SOX2 or CD24 resulted in a higher tolerance toward BRAFis, while the depletion of SOX2 via KD showed higher sensitivity. Similarly, the KD of CD24 in the more drug resistant SOX2 OE cells led to a restoration of sensitivity.…”
Section: Discussionsupporting
confidence: 83%
“…CD44 + /CD24 low/is one of the most studied breast cancer cell populations that is capable of tumour initiation and metastases, and results in adverse treatment outcomes (Sheridan et al, 2006;Deng et al, 2017). It has been shown (Deng et al, 2017) that in comparison to other triple negative breast cancer cell lines, MDA-MB-231 consists mostly of CD44 + /CD24cells with a relatively high resistance to doxorubicin and other anthracyclines. Our doxorubicin treated cultures displayed elevated transcriptional expression levels of both CD44 and especially of CD24 during the acute post-treatment period (DOX cultures), and returned to control levels during the recovery phase (DOX+1).…”
Section: Disscusionmentioning
confidence: 99%
“…Cluster of differentiation (CD) 24 is a small glycosyl phosphatidylinositol (GPI)-linked membrane glycoprotein (27)(28)(29)(30) amino acids in length) with glycosylation sites that bind P-selectin [7,8]. High expression levels of CD24 have been identified in various types of cancers-such as breast, prostate, pancreas, ovary, colorectal, and bladder cancers-and indicate poor prognosis [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%